Money talks. (New Humanist)
The article focuses on controversy emerges in the U.S. and Great Britain with the decision of technology company Apple to remove its 60 virtual private network (VPN) from its app store in China which create complicity in internet censorship. It mentions China has managed to use its influence with a large tech company to hit back against an array of different software developers. It also mentions Google took its search engines offline in China in 2010 after continued criticism over censorship.